Dexmedetomidine versus propofol for prevention of emergence delirium in pediatric cataract surgery: Double blinded randomized study - Ghada F. Amer; Maha Younis Abdallah (Egyptian Journal of Anaesthesia, 2022)
Background Emergence delirium (ED) is a common complication after general anesthesia in pediatrics, as reported by pediatric anesthesiologists. Multiple drugs have been suggested to prevent the incidence of this problem. Herein, we compared dexmedetomidine and propofol in the prevention of ED in pediatric patients undergoing cataract surgery under general anesthesia.Patients and methods: This prospective study included 80 children who were randomly allocated into two groups; the Dex group, which received dexmedetomidine, and the Pro group, which received propofol. All operations were performed under general anesthesia, and both drugs were administered 20 minutes before the end of surgery. Our primary outcome was to compare between the incidence of ED in both groups, while secondary outcomes included hemodynamic changes, pain scores, and other complications.Results Age, gender, and the duration of PACU stay showed no significant difference between the two groups. ED was encountered in 5% and 27.5% of patients in the Dex and Pro groups, respectively, with a significant decline in association with dexmedetomidine. Delirium and pain scores were significantly decreased in the Dex group throughout all times of measurement. The same group expressed a significant decrease in most heart rate and arterial pressure measurements. Hypotension was encountered in 15% of patients in the Dex group versus no cases in the Pro group.Conclusion Dexmedetomidine is superior to propofol in the prevention of ED in pediatrics. It is also associated with better post-operative pain scores.